Enhancing Students' Understanding of Integrated Social Sciences through Problem-Based Learning at MI Futuuhal Arifin - Lili Ernawati; Asmawati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students' understanding of Integrated Social Sciences (IPAS) at MI Futuuhal Arifin through the implementation of the Problem-Based Learning (PBL) model. IPAS is a complex subject that integrates multiple fields of study such as history, geography, and social studies, and requires students to develop critical thinking and problem-solving skills. Traditional teaching methods often fail to engage students deeply with the content, which can result in a superficial understanding. In contrast, the Problem-Based Learning model encourages active engagement by presenting students with real-world problems that require investigation and collaboration to solve. The research was conducted with a group of fifth-grade students at MI Futuuhal Arifin during the 2024 academic year. The study followed a cyclical process of planning, action, observation, and reflection. Data was collected through pre- and post-test assessments, classroom observations, and interviews with both students and teachers. The goal was to evaluate how PBL could improve students’ problem-solving skills, critical thinking, and understanding of IPAS topics. The results revealed a significant improvement in students’ engagement and understanding of IPAS concepts. Students demonstrated greater motivation to participate in class discussions and were more effective in solving problems related to social sciences topics. Moreover, the PBL model fostered collaboration among students, which enhanced their social and communication skills. By applying real-world problems to the lessons, students were able to connect theoretical knowledge with practical situations. In conclusion, the application of the Problem-Based Learning model at MI Futuuhal Arifin significantly improved students' understanding of IPAS. The research suggests that PBL should be integrated into the teaching strategies of other subjects to further promote active learning and critical thinking among students.